Characterization of the physical and phytochemical properties of optimally processed Chong-ak rice - Pomperada, Danica D.; Palomeno, Antonio (Quezon City University of the Philippines Diliman, 2025)
This study aimed to determine the optimal cooking conditions for the preparation of Chong-ak rice using full factorial design and response surface methodology (RSM). Specifically, the optimization and validation of predicted models for desirable properties, as well as the characterization of the optimally processed Chong-ak rice, are evaluated. Preliminary analysis revealed that the cooking method significantly (p-value < 0.05) affects the minimum cooking time of the rice. A three-level factorial optimization design utilizing nine different combinations of cooking methods and water:rice ratios highlighted significant (p-value < 0.05) differences in color characteristics—including L*, a*, b*, chroma, and hue angle—as well as antioxidant activity. Numerical optimization indicated that the rice cooking (RC) method with a water:rice ratio of 3.25:1 is optimum to maximize the a* value and antioxidant activity. Validation experiments revealed that the selected cooking method accurately predicted desirable color characteristics and antioxidant activity. Under optimal conditions, the cooked Chong-ak rice exhibited a water absorption ratio of 2.38 ± 0.0182, an elongation ratio of 1.37 ± 0.0912, and a total anthocyanin content (TAC) of 2.17 ± 0.3149 mg C3G/g. These findings offer practical applications for household cooking, potentially improving the retention of bioactive compounds during rice preparation. Furthermore, this study can be used as baseline information for future research on the preparation and utilization of pigmented rice.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Rice -- Philippines; Rice -- Processing; Cooking (Rice) -- Philippines; Optimization; Pigmented rice